Oligopolistic Pricing with Sequential Consumer Search - Stahl, Dale O. (American Economic Review, 1989)
N-identical stores compete by choosing prices for a homogeneous good with constant marginal costs. Consumers search sequentially with perfect recall. Some consumers have zero search costs, while all others have a positive search cost, c. There is a unique symmetric Nash Equilibrium price distribution that changes smoothly from "marginal cost pricing" to "monopoly pricing" as search cost and population parameters change. Remarkably, as the number of stores increases, the NE becomes more monopolistic.